2016
DOI: 10.1142/s0219455415500212
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Response of Triple Friction Pendulum Bearing under Near-Fault Ground Motions

Abstract: The seismic response of a stiff single-story and a flexible multi-story building isolated with triple friction pendulum bearing (TFPB) are investigated under the pulse-like (near-fault, NF-Pulse) and (NF-No Pulse) NF nonpulse ground motions. By varying the geometric parameters, such as the effective spherical surface radius, or by specifying different friction coefficients for each surface, one can adjust the behavior of the bearing. Consequently, the stiffness and damping ratio of the system can be optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, previous studies have shown that isolated structures are vulnerable to near-fault ground motions, especially the pulse-like motions. These excitations can impose significant demands, especially large isolator displacement, on the seismic responses of isolated structures, which can affect the feasibility of project [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have shown that isolated structures are vulnerable to near-fault ground motions, especially the pulse-like motions. These excitations can impose significant demands, especially large isolator displacement, on the seismic responses of isolated structures, which can affect the feasibility of project [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the optimum ranges for coefficient of friction and effective radius of curvature of all sliding surfaces are provided [3].…”
Section: Introductionmentioning
confidence: 99%